الأوزان العربية المستخدمة في المصطلحات المالية والبنكية والاقتصادية العربية الحديثة - Hanafi, Khalil Husni; Dollah, Nafi@Hanafi; Md. Sawari, Mohd. Fuad (Universiti Malaya, 2019)
The aim of this research is to highlight the features demonstrated by the modern Arabic language in understanding the modern financial, banking and economic terms by employing Arabic wording formulas, or wazan. The material of this study is limited to the Arabic terms used in "Islamic Electronic Dictionary of Financial, Banking and Economic Terms in Three Languages" (Hanafi et al., Trilingual Islamic Banking and Finance: Arabic-Malay-English). This research benefited from the descriptive analytical approach and examined the methods of the systematic linguistic dictionary and its important scientific contents, where terms were analyzed by a statistical analysis, showing the most important wording formulae, forms and meanings. The results show that the dictionary reflects about 700 terms by finding an interview with the terms in the Arabic words already known, wording formulas and significance. The wording formulas of the Arabic language used amounted to 28 formulae known in Arabic.